Kajian Macam Bokashi dan Varietas Terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) - Muhammad Syifa’; Ana Amiroh; Suharso Suharso (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2019)
Corn plants (Zea mays L.) are one of the second staple food plants after rice plants in Indonesia. Some people in Indonesia consume corn as a staple food. Given the importance of corn crop commodities, as one of the staple foods. So there needs to be an effort to increase the growth and production of corn plants. One such effort is the application of bokashi and varieties. This research was conducted in Kranji Village, Paciran District, Lamongan Regency. With the altitude of ± 5 meters above sea level. The time of the study was conducted from March to June 2019. This study uses Factorial Randomized Block Design (RBD), which consists of two factors, namely: bokashi and varieties. Each factor consists of 3 levels that are repeated 3 times, namely: the first factor, bokashi consists of 3 levels, namely without bokashi, bokashi cow cage, bokashi chicken coop. The second factor, the variety consisted of 3 levels namely BISI 18, NK7328 SUMO, and BISI 2. Observation of growth and production of maize plants includes vegetative phase (plant height and number of leaves) and generative phase (ear length, ear diameter, weight of peel cob ear off harvest, weight of peel cob off harvest per hectare and weight of 1000 seeds). The results showed the interaction between the treatment of bokashi and varieties on the height of maize plants and the treatment of NK7328 SUMO varieties had a good effect on all parameters of observation.